Groundwater depletion scenario in the north-eastern and south eastern part of Bangladesh - Kutub, Juel Rana (Journal of Nepal Geological Society, 2015)
Groundwater is one of the most important freshwater sources in Bangladesh which is used for drinking, household chores and irrigation. Due to high population pressure and excessive withdrawal, this important resource is under a lot of pressure. This study is designed to assess the present groundwater condition of the entire eastern region of Bangladesh. Groundwater depth data of 271 wells from 21 districts were collected from Bangladesh Water Development Board (BWDB) and analyzed in ArcGIS and Microsoft Excel software. During the pre-monsoon period, the groundwater lies beneath 2 to 14 meters of sediment. In the dry season, the groundwater remains between 4 and 12 meters in the northeastern part of Bangladesh. The larger values are mostly associated with urban areas. In case of southeastern part, groundwater level ranges from 2 to 8 meters. But the urbanized areas have groundwater levels in ranges in between 6 and 12. Compared to northern part, groundwater is found closer to surface in the southern part of the study area, Comilla, Mymensingh and Kishorganj. During monsoon season, there is a wide disparity of groundwater condition in the northeastern part, but southeaster part shows homogeneity. So, significant variation in groundwater depth (seasonal as well as spatial) is seen throughout the study area. The impact of urbanization is seen clearly which leads to lowering of groundwater level that can cause catastrophic events like earthquake, subsidence and pollution.